2015
DOI: 10.1016/j.physb.2014.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring intertwined orders in cuprate superconductors

Abstract: The concept of intertwined orders has been introduced to describe the cooperative relationship between antiferromagnetic spin correlations and electron (or hole) pair correlations that develop in copper-oxide superconductors. This contrasts with systems in which, for example, charge-density-wave (CDW) order competes for Fermi surface area with superconductivity. La$_{2-x}$Ba$_x$CuO$_4$ with $x=0.125$ provides an example in which the ordering of spin stripes coincides with the onset of two-dimensional supercond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 99 publications
(165 reference statements)
1
10
0
Order By: Relevance
“…One of the topical problems in the physics of high-T c cuprates is the coexistence and competition of the spin, superconducting, and charge orderings. The studying of the interplay between magnetism and superconductivity in cuprates has a long history [1,2,3]. Over the last fifteen years, a wealth of experimental results has suggested the presence of the charge ordering [4,5,6,7,8,9,10,11,12,13,14] and the interplaying spin and charge orderings [15,16,17,18,19,20,21] in cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…One of the topical problems in the physics of high-T c cuprates is the coexistence and competition of the spin, superconducting, and charge orderings. The studying of the interplay between magnetism and superconductivity in cuprates has a long history [1,2,3]. Over the last fifteen years, a wealth of experimental results has suggested the presence of the charge ordering [4,5,6,7,8,9,10,11,12,13,14] and the interplaying spin and charge orderings [15,16,17,18,19,20,21] in cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the point spread function of the pickup loop, the observed amplitude is a lower bound. The periods of the striae range between one and four microns, approximately a thousand times larger than the periods of stripe phases such as the spin and charge density waves that have been measured in bulk samples using neutron and x-ray diffraction techniques, [19][20][21] but comparable to the Pearl lengths in our films. Strikingly, we found that magnetic vortices tend to pin on the diamagnetic maxima of the striae, rather than the minima.…”
Section: Discussionmentioning
confidence: 60%
“…The coexistence of similar electronic phases has been explained in other cuprates as being intertwined in a spatially self-organized pattern with order parameters modulated along the c axis [36,37]. These systems (La 2−x Ba x CuO 4 , La 2−x−y Nd y Sr x CuO 4 , YBa 2 Cu 3 O 6+x ), however, all seem frustrated such that either bulk 3D superconductivity [38,39] or static antiferromagnetic order [40] is suppressed.…”
Section: Discussionmentioning
confidence: 86%